Applied social geography - Hilpert, Markus (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2002)
Why are there still problems concerning the management of spatial changes? Are spatial development projects really unique or are there typical patterns, which occur regularly? Is there a possibility to generalise such principles towards a 'theory of practice', which will be able to provide better management strategies for spatial development?
Keywords: družbena geografija; human geography; prostorsko planiranje; regionalno planiranje; socialna geografija; spatial planning